A relação construção conceitual/produção escrita de alunos que ingressam no ensino de 3ª grau da Unisc - Akele, Dercy (Signo, 2019)
A relação construção conceitual/produção escrita de alunos que ingressam no ensino de 3ª grau da Unisc